2014
DOI: 10.1063/1.4880742
|View full text |Cite
|
Sign up to set email alerts
|

Crystal facet effect on structural stability and electronic properties of wurtzite InP nanowires

Abstract: The crystal-facet effect on the structural stability and electronic properties of wurtzite InP nanowires (NWs) with different side-facets are investigated by using first-principles calculation within density-function theory. The surface-energy calculation suggests that side-facet structures of InP NWs are unreconstructed due to the fact that the low-index {11¯00} and {112¯0} facets with paired In-P dimers satisfy the electron counting rule. The calculated formation energies indicate that the structural stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…In the meanwhile, there is also a small amount (<10%) of WZ InP {1̅100} NWs observed due to the slightly larger in-plane lattice mismatch at the PdIn {110}/WZ InP {1̅100} interface as compared to the one of PdIn {110}/InP {2̅110}. These ⟨2̅110⟩ and ⟨1̅100⟩ orientations are nonpolar in wurtzite InP NWs as compared with typically observed polar ⟨0001⟩ orientation. , It should be noted that this in-plane lattice matching phenomenon contribute to the efficient NW growth with the excellent crystallinity and minimized defects via VSS mode as depicted in Figure b,c as compared with the commonly observed defective Au-catalyzed VLS grown InP NWs along ZB ⟨111⟩ and WZ ⟨0001⟩ directions. All these characteristics are also in good accordance with the previously reported Ni-catalyzed GaAs NW and Pd-catalyzed GaSb NW growth …”
Section: Resultsmentioning
confidence: 93%
“…In the meanwhile, there is also a small amount (<10%) of WZ InP {1̅100} NWs observed due to the slightly larger in-plane lattice mismatch at the PdIn {110}/WZ InP {1̅100} interface as compared to the one of PdIn {110}/InP {2̅110}. These ⟨2̅110⟩ and ⟨1̅100⟩ orientations are nonpolar in wurtzite InP NWs as compared with typically observed polar ⟨0001⟩ orientation. , It should be noted that this in-plane lattice matching phenomenon contribute to the efficient NW growth with the excellent crystallinity and minimized defects via VSS mode as depicted in Figure b,c as compared with the commonly observed defective Au-catalyzed VLS grown InP NWs along ZB ⟨111⟩ and WZ ⟨0001⟩ directions. All these characteristics are also in good accordance with the previously reported Ni-catalyzed GaAs NW and Pd-catalyzed GaSb NW growth …”
Section: Resultsmentioning
confidence: 93%
“…The result is very similar to the cases of InP and GaAs nanowires. 27,28 (iii) The VBM state in all four nanowire polytypes spatially spreads along their axis direction, but the CBM state in these nanowires indicates a different distribution. The CBM state displays a sawtooth-like distribution along {111}A facets in the 3C structure (Figure 5a) and an armchair-like distribution along the [0001] direction in the 2H structure (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, it is the reason why the size dependence of band gap in all four nanowire polytypes indicates similar trend, while the crystal phase effect only leads to a very small band gap difference (∼0.1 eV) among the nanowire polytypes. Although some previous studies have reported the importance of surface effect in electronic structures of III–V semiconductor nanowires, most of their results were obtained on the basis of bare or partly passivated nanowires. In the present study, all considered nanowires are passivated by hydrogens, and surface states of nanowires are eliminated by the hydrogen passivation.…”
Section: Resultsmentioning
confidence: 99%
“…To better evaluate the relative stability of the complex ZnO@(n, n) CNT structure, the formation energy ( E f ) of each encapsulated models were calculated using the following formula 35 : where E total is the total energy of the complex structure, E CNT and E ZnO represent the energy of individual CNT and ZnO, respectively. The calculated formation energies are depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%